2020
DOI: 10.1101/2020.02.11.943233
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural insights into secretory immunoglobulin A and its interaction with a pneumococcal adhesin

Abstract: AbstractSecretory Immunoglobulin A (SIgA) is the most abundant antibody at the mucosal surface. SIgA possesses two additional subunits besides IgA: the joining chain (J-chain) and secretory component (SC). SC is the ectodomain of the polymeric immunoglobulin receptor (pIgR), which functions to transport IgA to the mucosa. The underlying mechanism of how the J-chain and pIgR/SC facilitates the assembly and secretion of SIgA remains to be understood. During the infection of Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…However, the majority of interfacing residues appear to be conserved (Figure 1-figure supplement 1B). Consistent with these observations, comparison of our mouse SIgA with structures of dimeric forms of the human SIgA1 core (no Fabs), reported in the same timeframe as this work (Kumar, Arthur et al 2020, Wang, Wang et al 2020 revealed largely superimposable structures with some variability in contacts between complex components (not shown). The modeled positions of SC D2 are variable among structures, likely due to inherent flexibility in the domain's position, however, the structures have similar angles of bend (99 o in human SIgA and 97 o in mouse SIgA) and tilt (31 o in human SIgA and to 30 o tilt in mouse SIgA).…”
Section: Comparisons With Human Sigasupporting
confidence: 88%
See 1 more Smart Citation
“…However, the majority of interfacing residues appear to be conserved (Figure 1-figure supplement 1B). Consistent with these observations, comparison of our mouse SIgA with structures of dimeric forms of the human SIgA1 core (no Fabs), reported in the same timeframe as this work (Kumar, Arthur et al 2020, Wang, Wang et al 2020 revealed largely superimposable structures with some variability in contacts between complex components (not shown). The modeled positions of SC D2 are variable among structures, likely due to inherent flexibility in the domain's position, however, the structures have similar angles of bend (99 o in human SIgA and 97 o in mouse SIgA) and tilt (31 o in human SIgA and to 30 o tilt in mouse SIgA).…”
Section: Comparisons With Human Sigasupporting
confidence: 88%
“…Yet without the structures of the JC, dIgA and SIgA, interpreting biological data, understanding functional mechanisms and designing IgA-based therapeutics has remained a challenge. Our structures and related, human IgA structures published in the same timeframe as this work (Kumar, Arthur et al 2020, Wang, Wang et al 2020 provide an opportunity to addresses many outstanding questions surrounding SIgA and its functions as a mucosal antibody; we discuss a subset of them below and provide a model for formation, transport and function of SIgA in mammals.…”
Section: Siga Structure Impact On Antigen Bindingmentioning
confidence: 92%
“…The Ig-like domain is responsible for ligand binding 3 and shares about 40% sequence identity with the first Ig-like domain of polymeric immunoglobulin receptor (pIgR-D1), which is encoded by a gene located in the same chromosomal region in mammals 2 . However, rather than binding to both polymeric IgM and IgA as pIgR does 47 , FcμR exclusively binds to IgM 8 , indicating its specific binding mechanisms as well as functional roles. Potential residues responsible for the binding between IgM and FcμR have been proposed but the structure of the FcμR/IgM complex is currently unknown 911 .…”
Section: Main Textmentioning
confidence: 99%
“…It is the predominant antibody found in the mucosa-a vast extracellular environment constantly exposed to antigens from both pathogens and commensal bacteria-where it is secreted in the form of secretory IgA (SIgA). This is a multicomponent molecule comprised of two IgA monomers linked together by a joining chain (J chain) and covalently attached to the secretory component (SC) [2]. The secretory component wraps around the antibody complex and confers resistance to proteolytic degradation, along with protection in low pH environments.…”
Section: Introductionmentioning
confidence: 99%